Constructive Type Theory and the Dialogical Approach to Meaning - Shahid Rahman; Nicolas Clerbout (Baltic International Yearbook of Cognition, Logic and Communication, 2013)
In its origins Dialogical logic constituted one part of a new movement called the Erlangen School or Erlangen Constructivism. Its goal was to provide a new start to a general theory of language and of science. According to the Erlangen-School, language is not just a fact that we discover, but a human cultural accomplishment whose construction reason can and should control. The resulting project of intentionally constructing a scientific language was called the Orthosprache-project. Unfortunately, the Orthosprache-project was not further developed and seemed to fade away. It is possible that one of the reasons for this fading away is that the link between dialogical logic and Orthosprache was not sufficiently developed - in particular, the new theory of meaning to be found in dialogical logic seemed to be cut off from both the project of establishing the basis for scientific language and also from a general theory of meaning. We would like to contribute to clarifying one possible way in which a general dialogical theory of meaning could be linked to dialogical logic. The idea behind the proposal is to make use of constructive type theory in which logical inferences are preceded by the description of a fully interpreted language. The latter, we think, provides the means for a new start not only for the project of Orthosprache, but also for a general dialogical theory of meaning.
Keywords: type theory; dialogical logic; Orthosprache